[SOLVED] why am i not getting the same answer?

hi this is part of a question I was doing which wasn't really difficult, but i had a question about a section where I didn't get the same part using 2 methods...

I have to show: **m-n = (p-q)^3**

and the equations are: **2p^3 - 3(p+q)p + 6qp^2 = m**

and **2q^3 - 3pq - 3q^2 + 6pq^2 = n**

so if u simply subtract the 2 equations, you get the answer.. but i don't get it when i form 2 equations with:

**-3pq= ..... ** for both, and then equating their left sides

any suggestions?